Quality Perception of Short Food Supply Chains Products: From the Producer’s to the Consumer’s Point of View - Marina Acella; Alice Petrini; Roberta Bulgari; Andrea Ertani; András Sebök; Marco Devecchi; Silvana Nicola (International Journal of Food Studies)
Short food supply chains (SFSCs) are a still developing phenomenon in the world of food production and distribution. They involve a direct connection between local farmers and consumers, with minimal intermediaries involved. SFSCs have gained significant interest in recent years due to their potential to promote sustainable agriculture and support local communities. As a result, many governments, organisations, and individuals have been exploring ways to develop and promote these chains as a viable alternative to conventional food supply chains. However, it is still unclear how SFSCs products are perceived differently by producers and consumers: what makes SFSCs products more desirable? Starting from a European project (SmartChain), answers from twenty questionnaires from SFSCs actors across Europe were analysed to understand the strengths and weaknesses of SFSCs products according to the producers. From their answers, 18 quality criteria referred to SFSCs products were obtained and then proposed to consumers through a second questionnaire. The second questionnaire aimed to better understand whether the producers’ points of view matched the consumers’ points of view. From the analysis of the results, it was possible to understand what criteria were considered quality attributes by producers and consumers. Organic production and the presence of both trained and vulnerable personnel were not particularly relevant to the quality perception of SFSCs products. The storage method, the assortment range, and the processing of the products were not evaluated as quality criteria. The consumers who were interviewed perceived the quality of a food product coming from an SFSC linked to the characteristics of the social context of the product. They associated products sold in SFSCs with non-processed food. Overall, such a survey can be considered a useful tool to deepen our knowledge about short food supply chains and offers several ideas for further studies and analysis.